2020
DOI: 10.3390/polym12112607
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Scale Digital Image Correlation Analysis of In Situ Deformation of Open-Cell Porous Ultra-High Molecular Weight Polyethylene Foam

Abstract: Porous ultra-high molecular weight polyethylene (UHMWPE) is a high-performance bioinert polymer used in cranio-facial reconstructive surgery in procedures where relatively low mechanical stresses arise. As an alternative to much stiffer and more costly polyether-ether-ketone (PEEK) polymer, UHMWPE is finding further wide applications in hierarchically structured hybrids for advanced implants mimicking cartilage, cortical and trabecular bone tissues within a single component. The mechanical behaviour of open-ce… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…The composition of the 3D-printable RS-333 alloy from the Al-Mg-Si family considered in this paper was tuned by design to improve castability and thereby to provide a substitute for 6061 aluminium alloy in heat exchange applications. Mechanical microscopy methods that couple optical and/or electron microscopy with mechanical testing and advanced digital image analysis have been rapidly developing in recent decades [13][14][15][16][17]. These methods are particularly suitable for in situ mechanical testing of near-net-shape miniature and thin parts inside an SEM chamber, since the deformation and fracture behaviour can be visualised and studied at high resolution, readily Mechanical microscopy methods that couple optical and/or electron microscopy with mechanical testing and advanced digital image analysis have been rapidly developing in recent decades [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The composition of the 3D-printable RS-333 alloy from the Al-Mg-Si family considered in this paper was tuned by design to improve castability and thereby to provide a substitute for 6061 aluminium alloy in heat exchange applications. Mechanical microscopy methods that couple optical and/or electron microscopy with mechanical testing and advanced digital image analysis have been rapidly developing in recent decades [13][14][15][16][17]. These methods are particularly suitable for in situ mechanical testing of near-net-shape miniature and thin parts inside an SEM chamber, since the deformation and fracture behaviour can be visualised and studied at high resolution, readily Mechanical microscopy methods that couple optical and/or electron microscopy with mechanical testing and advanced digital image analysis have been rapidly developing in recent decades [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Mechanical microscopy methods that couple optical and/or electron microscopy with mechanical testing and advanced digital image analysis have been rapidly developing in recent decades [13][14][15][16][17]. These methods are particularly suitable for in situ mechanical testing of near-net-shape miniature and thin parts inside an SEM chamber, since the deformation and fracture behaviour can be visualised and studied at high resolution, readily Mechanical microscopy methods that couple optical and/or electron microscopy with mechanical testing and advanced digital image analysis have been rapidly developing in recent decades [13][14][15][16][17]. These methods are particularly suitable for in situ mechanical testing of near-net-shape miniature and thin parts inside an SEM chamber, since the deformation and fracture behaviour can be visualised and studied at high resolution, readily applicable to digital image correlation (DIC) analysis to reveal the peculiarities of deformation at the micrometre scale.…”
Section: Introductionmentioning
confidence: 99%
“…The plastic sleeper is manufactured and supplied by Replas plastic recycling company in Melbourne, Victoria, Australia, and it is made of post-consumer recycled plastics with fillers. The DIC method is a versatile and effective non-contact full-field technique of measurement that has been employed in various polymer composite research [54][55][56][57]. Sui et al (2018) [58] indicated that DIC technology is an accurate way of measuring full deflection profiles of beams under flexural bending.…”
Section: Sleeper Properties and Preparation For Dic Measurementsmentioning
confidence: 99%
“…Composition of 3D-printable RS-333 alloy from Al-Mg-Si system (which is considered in this paper) was tuned by design to improve castability and thereby to substitute 6061 aluminium alloy in heat exchange applications. Mechanical microscopy methods that couple optical and/or electron microscopy with mechanical testing and advanced digital image analysis have been rapidly developing in recent decades [14][15][16][17][18]. These methods are particularly suitable for in situ mechanical testing of near-net-shape miniature and thin parts inside SEM chamber, since the deformation and fracture behavior can be visualized and studied at high resolution readily applicable to digital image correlation (DIC) analysis to reveal the peculiarities of deformation at the micrometer scale.…”
Section: Introductionmentioning
confidence: 99%